Qualified precedents in the Superior Court of Justice: Jurimetric analysis of repetitive themes in social security law (Revista Direitos Humanos e Democracia, 2026)
The research proposes a jurimetrics study focused on the qualified precedents of the Superior Court of Justice (STJ). The study acknowledges that Law, as a normative science, is not neutral and requires an articulation between qualitative and quantitative methods for an objective understanding of the socio-legal phenomenon. To this end, the study employs the jurimetric method to collect, process, and analyze judicial data, focusing on 64 repetitive themes from the STJ, divided into 14 categories, four of which (procedural issues, rural activity, accident assistance, and special activity) account for 54.68% of the total. These themes were extracted from the official STJ database, using specific exclusion criteria such as validity and thematic relevance. The results show that 78.2% of the theses were established unanimously, demonstrating the solidity and coherence among the Court's justices. This is even more significant considering that changes in the composition of the First Section did not affect the final understanding of the themes. Thus, it is concluded that the STJ acts to unify and harmonize social security law, addressing claims with attention to the social context and promoting a collegial understanding essential for the stability of the legal system. Moreover, the findings suggest that by adopting a firm constitutional hermeneutics, the STJ contributes to strengthening trust in judicial decisions, reflecting the Court's institutional maturity in interpreting and applying social security law.
Keywords: Qualified Precedents; Social Security Law; Superior Court of Justice